Radioactive waste management Goi??nia - S??o Paulo: 30 years later - SOUZA, D.C.B. de (2018)
Considered the largest urban radiological accident in the world, the accident in Goi??nia with Cesium-137 resulted in the death of four people and injuries in another 49, besides measurable levels of internal or exter-nal contamination in 129. The accident generated also environmental contamination and thousands of tons of radioactive waste that resulted from the response activities. The accident occurred as a result of the disman-tling of an equipment of radiotherapy by employees of a junkyard. Before the accident was identified, con-taminated materials were sent to recycling companies in the state of S??o Paulo. The objective of this work was to report the existence of waste from Goi??nia accident in the state of S??o Paulo and to check the estimat-ed activities at the time of the waste conditioning by measuring the current dose rates in waste packages, allowing a refinement of previously applied calculations.